Comparison of distance sampling estimates to a known population size of Ant-eating Chats Myrmecocichla formicivora. (20th May 2016) - Stenkewitz, Ute; Herrmann, Eric
Abstract : Line-transect sampling was used to obtain abundance estimates of an Ant-eating Chat Myrmecocichla formicivora population to compare these with the true size of the population. The population size was determined by a long-term banding study, and abundance estimates were obtained by surveying line transects. The sampling effort was quadrupled to determine potential improvements in accuracy and precision. Abundance estimates of the single surveys differed up to 19.8% from the true number of birds and showed relatively high coefficients of variation. Estimates of the cumulative analyses only differed up to 5.8% while coefficients of variation improved considerably, and provided thus reliable population estimates compared with the true number of chats.